2017
DOI: 10.1002/ajhb.23044
|View full text |Cite
|
Sign up to set email alerts
|

Household fear of deportation in Mexican‐origin families: Relation to body mass index percentiles and salivary uric acid

Abstract: Key features of the social ecology in which mixed-status families are embedded are associated with individual differences in biological processes linked to increased risk for chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…Data collection occurred in the summer/fall of 2014 in Phoenix AZ. More detailed description of the recruitment of families for this study can be found in other publications ( Martínez et al, 2017a , Martínez et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection occurred in the summer/fall of 2014 in Phoenix AZ. More detailed description of the recruitment of families for this study can be found in other publications ( Martínez et al, 2017a , Martínez et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, scholars have demonstrated that a precarious legal status can impact the health of immigrants in a variety of direct and indirect ways, from directly affecting physical heath, such as fear-induced headaches and weakened digestion (Aranda and Vaquera, 2015;Gonzales and Chavez, 2012), to limiting their access to medical services (Arcury and Quandt, 2007;Gómez Cervantes and Menjívar, 2020;Joseph and Marrow, 2017;Vargas et al, 2017), creating anxiety and depression that affects these immigrants' psychological well-being (Gonzales and Chavez, 2012;. More specifically, fear of deportation has been linked to poor physical health (Ayón 2018;Enriquez et al, 2018;Martínez et al, 2017), increased risks of depression and nervousness, substance abuse, and post-traumatic stress disorder (Brabeck and Xu, 2010;Garcia 2018;Moya Salas and Ayón, 2013;Sullivan and Rehm, 2005;. Indeed, some researchers have argued that undocumented status is inimical to health and well-being (McGuire and Georges, 2003;Van Natta et al, 2019) and that illegality itself can be a health risk (Castañeda 2009;Gómez Cervantes and Menjívar, 2020).…”
Section: Illegality Discrimination and Psychological Distress Among Us Latinxsmentioning
confidence: 99%
“…Future research might model human biology research that routinely combines MICBS with psychosocial frameworks. For example, social determinants of health frameworks (see Marmot, 2005) have been used to understand multilevel environmental exposures (see Dufour, 2006) within socioeconomic and political contexts (Levy et al, 2016;Liebert et al, 2013;Martínez, Ruelas, & Granger, 2017 ;Thompson, Nicholas, Watson, Terán, & Bentley, 2019;Wutich & Brewis, 2014). Investigating the social, economic, and political factors shaping the biologies of everyday life among TGD people is critically important for future research.…”
Section: Structural Violence and Biologies Of Everyday Lifementioning
confidence: 99%